(untitled) - Pejovic, Vladimir (Oxford, New York, 1999)
A series providing comprehensive preparation for the IELTS. Now with Practice Tests with annotated key.
Keywords: English language,English language,International english language testing system; Examinations, questions, etc,Textbooks for foreign speakers